Ownership and commodification of human biological materials: ethical and legal dilemmas - Munasinghe, B.M. (Faculty of Law, University of Colombo, 2021)
The ownership of human biological materials is a controversial issue because of its legal and ethical considerations. Some scholars argue that people should retain ownership of their biomaterials indefinitely. On the other hand, researchers argue that granting property rights over human bio samples via ownership will convert human bio materials into a commodity by preventing the development of the research industry. Therefore, the law expresses hesitation about construing the meaning of the human body or its biomaterials in terms of ownership because owning oneself can result in the recreation of the concept of slavery. This paper aims to examine the ethical and legal difficulties surrounding ownership and use of biological material and products that originate from humans, including those used for commercial purposes. This research was conducted primarily as qualitative research based on primary and secondary data. The paper is divided into three sections. Firstly, the paper examines the concept of ownership and its nature by using Tony Honoré's analysis on the social constructivist theory of ownership. Secondly, it moves onto denote the legal and ethical complications and concerns relating to human biomaterials with special reference to the concept of the commodification of biomaterials. Thirdly, the research paper considers the pros and cons of granting ownership rights over human biomaterials and emphasises the importance of having specific legal recognition of human biomaterials by analysing the law relating to human biological materials in India with particular reference to the amended Transplantation of Human Organs and Tissues Act 1994 and National Organ Transplant Program. This paper suggests that ownership rights should be granted over human biological materials under a property law regime. At the same time, lawmakers should adopt an ethical framework that has universal binding authority to address the issues related to the commodification of human biomaterials.
Keywords: human biomaterials; ownership; social constructivist theory; commodification